2001
DOI: 10.1046/j.1365-2052.2001.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous domestic breeds as reservoirs of genetic diversity: the Argentinean Creole cattle

Abstract: Contrary to highly selected commercial breeds, indigenous domestic breeds are composed of semi-wild or feral populations subjected to reduced levels of artificial selection. As a consequence, many of these breeds have become locally adapted to a wide range of environments, showing high levels of phenotypic variability and increased fitness under natural conditions. Genetic analyses of three loci associated with milk production (alpha(S1)-casein, kappa-casein and prolactin) and the locus BoLA-DRB3 of the major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 47 publications
5
47
0
7
Order By: Relevance
“…An early indication of the influence of African breeds in the origin of Creole cattle is given in Giovambattista et al (2001), which describes the existence of two particular alleles of BoLA-DRB3 in Argentinean Creole cattle that were never mtDNA diversity in South American cattle PM Mirol et al detected in European breeds, but were reported in African indigenous breeds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An early indication of the influence of African breeds in the origin of Creole cattle is given in Giovambattista et al (2001), which describes the existence of two particular alleles of BoLA-DRB3 in Argentinean Creole cattle that were never mtDNA diversity in South American cattle PM Mirol et al detected in European breeds, but were reported in African indigenous breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies based on polymorphism at loci related to milk production and immune response and on microsatellites have detected genetic structure among the Argentinean and Bolivian populations of cattle (Liró n et al, 2000; Giovambattista et al, 2001). An AMOVA based on the mitochondrial sequences was conducted in order to analyse the distribution of this variability.…”
Section: Cc1 8 a C T T A C A T A T G A C T A A G T G T T A G T T A Amentioning
confidence: 99%
See 1 more Smart Citation
“…The F ST and the exact test for genetic differentiation showed a significant subdivision of the Bolivian and Argentine Creole cattle population. This heterogeneous genetic pattern seems to be a major characteristic of American Creole breeds (Russell et al, 2000;Giovambattista et al, 2001) and could be the consequence of the subdivision of Creole cattle from this region into small herds, isolated or with a low degree of gene flow among them, and adapted to a wide range of environments. In concordance with this hypothesis, a lower level of average heterozygosity was observed in the Patagonian Creole cattle breed, which is the most isolated population.…”
Section: Discussionmentioning
confidence: 99%
“…2001) and, principally, source of traits selected and fixed mainly by the influence of the environment (Hall & Ruane, 1993). Mirkena et al.…”
Section: Introductionmentioning
confidence: 99%